Graphene functionalized bio-carbon xerogel for achieving high-rate and high-stability supercapacitors. (20th August 2018) - Yang, Xi; Jiang, Zehui; Fei, Benhua; Ma, Jianfeng; Liu, Xinge
Abstract: Biomass carbons have attracted considerable attention in the pursuit of cheap and renewable electrode materials. However, a low-energy route (like hydrothermal carbonization) is still a challenge for achieving bio-carbon electrodes with high-performance. Herein, a high-rate and high stability supercapacitor was fabricated based on graphene functionalized bio-carbon xerogel. The supercapacitor shows comparable or even higher performance than reported supercapacitors derived from bio-carbons and graphene-based materials, which can be attributed to sandwich-like porous structure that carbon spheres interspersed between porous graphene nanoplatelets. It demonstrates a superior specific capacitance of 139 F g −1  at a superhigh current of 100 A g −1 in an aqueous electrolyte, maintaining 73.5% of that at 1 A g −1 (189 F g −1 ). More importantly, the device retains 100% of initial specific capacitance, energy density and power density after 10000 cycles at 5 A g −1 . This work paves the way to develop renewable supercapacitors based on low-cost biomass resources and low-energy fabrication.